2009
DOI: 10.1093/jxb/erp227
|View full text |Cite
|
Sign up to set email alerts
|

Gene regulation in parthenocarpic tomato fruit

Abstract: Parthenocarpy is potentially a desirable trait for many commercially grown fruits if undesirable changes to structure, flavour, or nutrition can be avoided. Parthenocarpic transgenic tomato plants (cv MicroTom) were obtained by the regulation of genes for auxin synthesis (iaaM) or responsiveness (rolB) driven by DefH9 or the INNER NO OUTER (INO) promoter from Arabidopsis thaliana. Fruits at a breaker stage were analysed at a transcriptomic and metabolomic level using microarrays, real-time reverse transcriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 45 publications
5
41
0
5
Order By: Relevance
“…AF416289.1), which is expressed in tomato ovary (Vriezen et al, 2008) and fruit (Martinelli et al, 2009), was found in our analysis to be transiently up-regulated 2 h after flower removal in both AZ and NAZ samples (Fig. 6H).…”
Section: Effect Of Flower Removal On the Expression Of Auxin-related mentioning
confidence: 56%
“…AF416289.1), which is expressed in tomato ovary (Vriezen et al, 2008) and fruit (Martinelli et al, 2009), was found in our analysis to be transiently up-regulated 2 h after flower removal in both AZ and NAZ samples (Fig. 6H).…”
Section: Effect Of Flower Removal On the Expression Of Auxin-related mentioning
confidence: 56%
“…Schijlen et al (2007) constitutively suppressed CHS expression in tomato via RNA interference and obtained pink tomatoes due to a reduction of cuticle flavonoids. However, the alteration of plant reproduction due to pollen growth impairment present in these plants led to the development of parthenocarpic fruits, which are known to have altered hormone levels as well as several genes involved in cell wall, sugars, and lipid metabolism (Martinelli et al, 2009).…”
mentioning
confidence: 99%
“…The strategy is to focus on tomato genes that were differentially regulated by TSWV infections, previously identified by published works. Molecular markers commonly used for phylogenetic studies (Martinelli et al, 2008;Martinelli et al, 2009b;Minnocci et al, 2010) maybe also employed to determine untargeted effects on genomic structure. The analysis of the phenotype will be performed measuring key morphological parameters such as leaf, stem, whole plant dimension, length, size and health.…”
Section: Molecular and Phenotypic Evaluation Of Genetic Resistancementioning
confidence: 99%